2018
DOI: 10.5606/archrheumatol.2018.6394
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Pentraxine 3 Levels and Hematological Markers in Patients With Rheumatoid Arthritis

Abstract: Objectives: This study aims to investigate the association of pentraxin 3 (PTX3) with neutrophil/lymphocyte ratio (NLR) rather than the disease activity score 28 using C-reactive protein in rheumatoid arthritis (RA). Patients and methods:The study included 59 RA patients (11 males, 48 females; mean age 53.79±13.55 years; range 40 to 66 years) and 20 healthy controls (5 males, 15 females; mean age 50.41±6.11 years; range 43 to 56 years). Complete blood count tests were recorded and NLR and platelet/lymphocyte r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Here, for the first time, we analyzed PTX3 expression profiles in a cohort of early and treatment-naïve RA patients at baseline, and 6-months after cs-DMARD treatment. As previously described, we confirmed that RA patients presented a higher concentration of circulating PTX3 compared to healthy donors (13)(14)(15) and that PTX3 levels positively correlated with CRP (16). In addition, we showed that, at the onset of the disease prior to any treatment modification, circulating PTX3 levels also correlated with ESR, DAS28 and the count of swollen and tender joints, therefore being a strong marker of disease activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Here, for the first time, we analyzed PTX3 expression profiles in a cohort of early and treatment-naïve RA patients at baseline, and 6-months after cs-DMARD treatment. As previously described, we confirmed that RA patients presented a higher concentration of circulating PTX3 compared to healthy donors (13)(14)(15) and that PTX3 levels positively correlated with CRP (16). In addition, we showed that, at the onset of the disease prior to any treatment modification, circulating PTX3 levels also correlated with ESR, DAS28 and the count of swollen and tender joints, therefore being a strong marker of disease activity.…”
Section: Discussionsupporting
confidence: 89%
“…In the context of RA, PTX3 has been shown to be constitutively highly expressed by synovial fibroblasts (12); however, as described in other tissues, various resident or infiltrating synovial cells like macrophages or endothelial cells might also represent a source of PTX3 upon inflammatory activation. Several groups found that PTX3 is upregulated in the serum of RA patients compared to healthy donors (13)(14)(15) or patients with osteoarthritis (16). However, conflicting results have been published regarding the relationship between the level of PTX3 in the serum and clinical features of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PTX3 is indirectly affected by the expression of IL-6 103 . Therefore, PTX3 and IL-6 are not directly interrelated, but IL-6 may indirectly induce the expression of PTX3 to promote the formation of inflammatory microenvironment of RA 104 .…”
Section: Pentraxin 3 With Cardinal Ra-involved Molecule Ensemblementioning
confidence: 99%